Anxiety and vital signs in cancer patients and music students before and after a music intervention: a quasi-experimental pilot study - Caballero-de-la-Calle, Raquel; Ferrero-Sereno, Patricia; García-Garrido, Miguel Ángel; Ruiz-Rodríguez, Ana; Moro-Tejedor, María Nieves; Leñero-Cirujano, Miriam (My University, 2025)
to analyze the level of anxiety and variation in the vital signs of cancer patients and performers (music students) before and after a live musical intervention. quasi-experimental pilot study with no control group. An interdisciplinary musical intervention was carried out between Nursing and Music Performance students. The level of anxiety was assessed with the Hamilton scale and the variation in vital signs before and after the intervention in a day hospital in cancer patients and in interpreters, in the latter the variables were also analyzed before and after the intervention. The Wilcoxon test was used to analyze the data. 18 patients and 10 music students took part. Variations in vital signs were observed in both groups, as well as a decrease in the level of anxiety in the patients at the post-intervention moment. In the students, the level of anxiety was higher at the beginning of the dress rehearsal compared to the rest of the evaluated moments at the hospital. live music interventions could improve anxiety levels in both cancer patients and performers.